Characterization of the Key Odorants of Mastic Gum (Pistacia lentiscus var. Chia) from Two Different Countries - Ozlem Kilic-Buyukkurt; Gamze Guclu; Hasim Kelebek; Serkan Selli (Applied Sciences)
Mastic gum, a plant-based resin from mastic trees, has become very popular in recent years and has been used in various food products due to its strong and positive aroma properties. In the present study, key odorant compounds of the mastic gum (MG) samples obtained from mastic gum trees (Pistacia lentiscus var. Chia) from two different countries, Türkiye (MGT) and Greece (MGG), were investigated and compared. The aroma-active compounds (AACs) were determined by aroma extract dilution analysis (AEDA) and by using gas chromatography-mass spectrometry-olfactometry (GC-MS-O). The two mastic gum samples exhibited similar aroma profiles but significant differences were observed in their concentrations. Among the aroma groups identified in both samples, monoterpenes were the most abundant group with α-pinene as the main compound followed by β-myrcene and β-pinene. On the other hand, the most dominant AAC in both samples was determined to be α-pinene (resinous, forest-like odor), followed by β-pinene (resinous, terpene-like odor), β-myrcene (pine-like, greenish odor), and linalool (floral, fruity odor), all of which had high flavor dilution (FD) values. The findings of the AEDA and sensory analysis revealed that the MGT sample contained more floral and fruity odors while the MGG sample had more resinous and pine-woody odors.